Fluid Intake and Risk of Male Urinary Incontinence - Lee, Andy; Hirayama, Fumi (Taipei: Taiwanese Continence Society: Taiway urogynecology Association, 2012)
Objective: To investigate whether fluid intake is associated with urinary incontinence (UI) in men. Methods: A total of 700 men from 40 to 75 years old were recruited from the community in central and southern Japan. A validated food frequency questionnaire was administered face-to-face to obtain information on habitual beverage consumption. UI status was ascertained using the International Consultation on Incontinence Questionnaire-Short Form. Logistic regression analysis was conducted to assess the relationship between total fluid intake and the prevalence of UI. Results: Among the 683 eligible participants (mean age 62 years), 49 men (7.2%) experienced urine leakage for the past 2.6 (standard deviation [SD] 1.9) years. The mean daily fluid intake was slightly higher (p=0.08) among incontinent men (1766, SD 1171 mL) than those without the condition (1460, SD 918 mL). However, the increases in risk of UI at higher levels of fluid intake were not significant after accounting for age and other confounding factors. Conclusion: Little association was evident between fluid intake and UI in middle-aged and older Japanese men.